Design and performance of a compact stick-slip type piezoelectric actuator based on right triangle flexible stator - Wang, Liang; Wang, Heran; Cheng, Tinghai (Smart materials and structures, 2022)
In the field of stick-slip type piezoelectric actuators, the actuator with simple and compact structure has been given significant research and design value. A compact stick-slip piezoelectric actuator based on right triangle flexible stator is proposed and evaluated in this work. The proposed actuator only includes a right triangular type stator inserted with a PZT stack and it has the merit of simple structure. The PZT stack is excited under a sawtooth waveform voltage, and the elongation deformation of the PZT stack makes the driving foot move obliquely due to the right triangular stator. The slider is pressed under the vertical component of the oblique movement, while the slider is actuated under the horizontal component simultaneously. The working principle of the proposed actuator is illustrated by theoretical and simulation methods in detail. The proposed actuator is fabricated and its output characteristics are measured. The experimental results show that the maximum output speed of the developed actuator is 4.6 mm s −1 when the voltage and frequency are 100 V and 720 Hz. It has the merit of simple design and relatively better performance by series of comparisons with some existing works.